The essence and peculiarity of the linguistic identity of the Sakha youth in contemporary sociocultural context - Ivanova, Nina I. (The New Research of Tuva, 2022)
The article discusses the nature of the linguistic identity of contemporary Sakha youth living in Yakutsk, the Republic of Sakha (Yakutia), including the aspect of its dynamics. It is based on the research data obtained during ethnic, social, psychological and linguistic monitoring that was conducted in 2007, 2014 and 2021.The consistency of the ethnolinguistic identity of the Sakha youth under the acute influence of external factors (an objective decrease in language competence, deterioration of active skills and improvement of passive ones) has been determined. The communicative strategy is characterized by the substitution of linguistic competence with sociolinguistic competence and accommodation. A significant sociolinguistic characteristic of the youth is the availability of ethnolinguistic resources for the reproduction of their native language. They are in a very inert state due to the transformation of the oncoming generation’s values, the degradation of the conditions of bilingualism under the influence of linguistic and political as well as socioeconomic factors, the negative impact of mass digitalization.
Keywords: Yakut language; Sakha; Sakha youth; Republic of Sakha; native language; linguistic self-identification; linguistic competence; language mindset; language policy